2016
DOI: 10.1111/jcom.12266
|View full text |Cite
|
Sign up to set email alerts
|

I Saw You in the News: Mediated and Direct Intergroup Contact Improve Outgroup Attitudes

Abstract: This study extends the boundary conditions of mediated contact theory by (a) differentiating between mediated contact quantity and quality, (b) examining whether mediated contact exerts effects above and beyond direct contact, and (c) offering causal and generalizable evidence on the effects of exposure to numerous individual outgroup members in news media. We match individual‐level data from a representative panel survey with data on the amount of coverage about members from two outgroups and with the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…Due to its audio‐visual nature, television serves as a key source of information for impressions that in‐group members may have of other social groups, makes the identities and characters of out‐group members’ salient to viewers, and in this way approximates face‐to‐face intergroup contact. Accordingly, previous research suggests that television represents an effective mechanism to influence beliefs and attitudes concerning less encountered out‐groups (Garretson, ; Hoffner & Cohen, ; Mutz & Goldman, ; Wojcieszak & Azrout, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its audio‐visual nature, television serves as a key source of information for impressions that in‐group members may have of other social groups, makes the identities and characters of out‐group members’ salient to viewers, and in this way approximates face‐to‐face intergroup contact. Accordingly, previous research suggests that television represents an effective mechanism to influence beliefs and attitudes concerning less encountered out‐groups (Garretson, ; Hoffner & Cohen, ; Mutz & Goldman, ; Wojcieszak & Azrout, ).…”
Section: Introductionmentioning
confidence: 99%
“…viewers, and in this way approximates face-to-face intergroup contact. Accordingly, previous research suggests that television represents an effective mechanism to influence beliefs and attitudes concerning less encountered out-groups (Garretson, 2015;Hoffner & Cohen, 2015;Mutz & Goldman, 2010;Wojcieszak & Azrout, 2016).…”
mentioning
confidence: 99%
“…Pettigrew and Tropp's (2006) meta-analysis supports these effects and patterns of intergroup contact. However, such direct contact is not always feasible; people tend to choose their social contact based on the similarities in social categories (e.g., race, gender, sexuality, class, religion) (Wojcieszak & Azrout, 2016). In reality, most people do not have direct interpersonal contact with most outgroups that fall outside their identities, especially when it comes to marginalized social groups such as the transgender community.…”
Section: Intergroup Contactmentioning
confidence: 99%
“…Although underexplored, the existing research on mediated vicarious contact identifies not only the attitude reshaping effects but also the conditions maximizing such effects. According to these studies, how much the audience identifies with the ingroup characters in the observed intergroup interaction (e.g., Joyce & Harwood, 2014), how positively they perceive the contact experience of the ingroup and outgroup characters (e.g., Mazziotta, Mummendey, & Wright, 2011), and the quantity of mediated outgroup contact have positive impact on intergroup attitude outcomes (Wojcieszak & Azrout, 2016). However, this line of research has not examined how narrative strategies such as narrative perspective might impact the cognition of the depiction of intergroup interaction.…”
Section: Mediated Vicarious Contact: Intergroup Interaction In the Mediamentioning
confidence: 99%
“…In order to present such a condition to children, we decided to make it as systematically and pragmatically appropriate as we could, and thus compromised on answering every other question that children asked. On the other hand, studies on indirect intergroup contact indicate that the more exposure one gets, the more substantial is the change in one's attitudes (Wojcieszak & Azrout, ). We thus hoped that a comparison of the Full vs.…”
Section: Introductionmentioning
confidence: 99%